THE RELATIONSHIP BETWEEN PHYSICAL EXERCISE AND MENTAL HEALTH IN STUDENTS (CIPEEX, 2022)
INTRODUCTION: MENTAL HEALTH REFERS TO A WELLBEING IN WHICH THE INDIVIDUAL DEVELOPS PERSONAL SKILLS, CAN COPE WITH THE STRESSES OF LIFE, WORKS PRODUCTIVELY AND IS ABLE TO CONTRIBUTE TO THE COMMUNITY, AND PHYSICAL EXERCISE IS A POSSIBLE ALLY TO MAINTAIN THIS STATE OF WELLBEING.